Book review "management of financial services in contemporary business conditions" - Vunjak, N. M., Dragosavac, M. M., Lukić Nikolić, J., Davidov, T., Mihajlović, M., Management of Financial Services in Contemporary Business Conditions, Modern Business School, Belgrade, 2024 - Mirković Vladimir (Bankarstvo)
Book review: Vunjak, N. M., Dragosavac, M. M., Lukić Nikolić, J., Davidov, T., Mihajlović, M. (2024). Management of Financial Services in Contemporary Business Conditions. Belgrade: Modern Business School. ISBN - 978-86-87677-33-3 COBISS.SR-ID - 152899593